Race discrimination in Brazil: An analysis of the age, period and cohort effects - Maurício Cortez Reis; Anna Risi Vianna Crespo (Institute for Applied Economic Research (ipea), 2015)
Earnings differential between white and black workers present a decreasing trend for younger cohorts in Brazil. We argue in this paper that the reduction in economic discrimination for younger cohorts could have played an important role on this result. Using the Brazilian National Household Sample Survey data [Pesquisa Nacional por Amostra de Domicílios (PNAD)] from 1987 to 2002, the earnings differential by race is decomposed into two parts through the Oaxaca-Blinder methodology: the first one is the characteristic effect and the second is the discrimination term. This decomposition is made for 90 cells defined by cohort and year. After that, the amount of earnings differential due to discrimination term is decomposed into age, period and cohort effects. According to the evidences, the cohort effects are smaller for younger generations, and the age effects present a decreasing trend for older workers. The results show also that periods with high inflation are associated with weaker contribution of discrimination term to earnings differential.
Keywords: J7; J11; J15; 330